Adoption of artificial intelligence by librarians for effective service delivery in academic libraries in Edo State - Akpukpu, Akhimien Omono Vera; Osawele, Rachael Ekeikhomen (Communicate: Journal of Library and Information Science, 2025)
The adoption of Artificial Intelligence into library services is transforming the way librarians manage and deliver information. Artificial intelligence applications in libraries include automation of cataloging and inventory management which increases efficiency and accuracy by utilizing machine learning algorithms to classify and organize materials. Artificial intelligence offers instant support for user inquiries, facilitating better service and freeing up librarians to focus on more complex tasks. Additionally, Artificial intelligence enhances user engagement through personalized book recommendations based on analysis of borrowing patterns and preferences. The use of artificial intelligence in research assistance further supports academic endeavors by efficiently searching databases and summarizing relevant literature. Moreso, predictive analytics enabled by Artificial intelligence aids in collection development by forecasting future needs and trends. Despite its benefit, the implementation of Artificial intelligence requires careful consideration of data privacy and ethical concerns. This overview underscored the potential of Artificial intelligence to revolutionize library services while highlighting the importance of responsible application to maximize its advantages.